2001
DOI: 10.1074/jbc.m006102200
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage and Shedding of E-cadherin after Induction of Apoptosis

Abstract: Apoptotic cell death induces dramatic molecular changes in cells, becoming apparent on the structural level as membrane blebbing, condensation of the cytoplasm and nucleus, and loss of cell-cell contacts. The activation of caspases is one of the fundamental steps during programmed cell death. Here we report a detailed analysis of the fate of the Ca 2؉ -dependent cell adhesion molecule E-cadherin in apoptotic epithelial cells and show that during apoptosis fragments of Ecadherin with apparent molecular masses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
230
2
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 253 publications
(246 citation statements)
references
References 70 publications
10
230
2
4
Order By: Relevance
“…MAGI-1 itself has been shown to localise to tight and adherens junctions [28], where it interacts with the β-catenin-E-cadherin complex [26], with the synaptopodin and alphaactinin-4 actin binding proteins [28], and with the JAM4 cell adhesion protein [29]. β-catenin was the first protein involved in regulating cell contact that was shown to be cleaved by caspases during apoptosis [6] and E-cadherin is also known to be cleaved by caspases during apoptosis [12]. The data presented here demonstrates that MAGI-1 cleavage occurs at a similar time as β-catenin and E-cadherin cleavage during apoptosis (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MAGI-1 itself has been shown to localise to tight and adherens junctions [28], where it interacts with the β-catenin-E-cadherin complex [26], with the synaptopodin and alphaactinin-4 actin binding proteins [28], and with the JAM4 cell adhesion protein [29]. β-catenin was the first protein involved in regulating cell contact that was shown to be cleaved by caspases during apoptosis [6] and E-cadherin is also known to be cleaved by caspases during apoptosis [12]. The data presented here demonstrates that MAGI-1 cleavage occurs at a similar time as β-catenin and E-cadherin cleavage during apoptosis (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, caspase activity (DEVD-ase activity) was largely increased (~ 10-fold after 16 h; data not shown). Cleavage of E-cadherin, which is an important player in establishing and maintaining cell-cell contacts (for review [37]), and which is a known caspase target [12], was also followed during UV irradiation-induced apoptosis. The first cleavage products were also observed 4 h post induction of apoptosis ( Fig.…”
Section: Magi-1 Is Cleaved By Caspases During Uv Irradiation-and Staumentioning
confidence: 99%
See 1 more Smart Citation
“…During recent years a number of caspase substrates have been identified. Among these, cytoskeletal proteins and regulators (Brancolini et al, 1995;Jaenicke et al, 1998) and components of cell-cell adhesion complexes such as cadherins (Herren et al, 1998;Schmeiser and Grand, 1999;Steinhusen et al, 2001) and catenins (Brancolini et al, 1998;Schmeiser et al, 1998;Steinhusen et al, 2000) contribute to the disruption of the cytoarchitecture. Furthermore, we recently showed that desmosomal proteins are targeted by caspases .…”
mentioning
confidence: 99%
“…The mechanisms that lead to the loss of E-cadherin expression in the cell membrane are still unclear. The disruption of cell-to-cell adhesion might be mediated by several factors, such as digestion by proteases (Lochter et al, 1997;Steinhusen et al, 2001), transcriptional repression (Batlle et al, 2000;Cano et al, 2000;Yap et al, 2007), endocytosis (Fujita et al, 2002), mutations in the E-cadherin gene (Oda et al, 1994;Saito et al, 2001) and methylation of E-cadherin promoter (Yoshiura et al, 1995).…”
Section: Discussionmentioning
confidence: 99%